(untitled) (American Journal of Islam and Society, 2009)
Negar Mottahedeh’s book contains an important analysis of the relationship between Babism and modernity in Iran. The author argues that in order to understand “the historical conditions for Iranian perceptions of modernity” (p. 236), scholars need to break away from traditional disciplinary systems, just as Babism itself went against traditional understandings of Shi`ism in Iran. It is a complex, highly reflexive, and ambitious proposal. The book’s detailed historical account of the emergence of the Bab and the critical lens through which the author analyzes the impact of Qurrat al-Ayn Tahirih’s figure on the Iranian perceptions of the modern woman are bound to inspire any serious student of Iranian modernity. The figures of the Bab and Qurrat al-Ayn Tahirih are analyzed against the backdrop of the deeply ingrained images of the ta`ziyeh, Fatimah, and Joseph, as well as Qur’anic images of Paradise and houris in Iranian culture. I have come away with a deeper understanding of the Iranian psyche and cultural attitudes toward modernity with their unfathomable embrace of traditional and religious motifs. The book’s underlying questions are “Why are modern acts, often articulated in terms of dress or veiling, associated with the dissent of the Babi? And why does this image of ‘the Babi’ appear as a dialectic of modernity, fluctuating between images ofWestern secularism and unveiling on the one hand, and as unpresentable images of Shi`ite antiquity, on the other?” (p. 236). The reader does not get an answer addressing either the “why,” identifying the causes for this phenomenon, or an ethnographic account of how modern Iranian society grapples with the antique elements of Shi`ite Islamic thought. Instead, the author sets out to map the influences of the ta`ziyeh on Iranian cultural modernity in an “anti-disciplinary” fashion – just as Babism should be understood in relation to Shi`ite thought infused with Iranian nationalism ...